1974
DOI: 10.1007/bf00388267
|View full text |Cite
|
Sign up to set email alerts
|

The entry of ions and molecules into roots: an investigation using electron-opaque tracers

Abstract: Various solutions containing ions or molecules which may be visualized in the electron microscope have been presented to barley (Hordeum vulgare L.) roots. Large molecules such as gold sol particles (<6.0 nm) or ferritin (approx. 12.0 nm) were not found to be taken into the cytoplasm of any cells. Very dilute solutions of uranyl acetate or lanthanum nitrate resulted in the presence of typical electron-opaque crystals in the cortical apoplasm, as well as in cytoplasmic vesicles of cortical and some endodermal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
2
2

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 18 publications
4
27
2
2
Order By: Relevance
“…This property to interrupt the cell wall continuity was already investigated in 1910, with a study of the penetration of some salts into the root that provided evidence that several salts needed to pass through the endodermis symplast in order to reach the stele (de Rufz de Lavison, 1910). Later, many studies reported that the diffusion of fluorescent dyes or ions is blocked at the level of the endodermis and that this coincides with the presence of the CS (Clarkson and Sanderson, 1969;Robards and Robb, 1974;Singh and Jacobson, 1977;Peterson, 1987). Recently, studies in Arabidopsis employed propidium iodide (PI) as a tracer for the apoplastic route (Alassimone et al, 2010).…”
Section: Three Routes For Nutrients the Apoplastic Pathwaymentioning
confidence: 99%
“…This property to interrupt the cell wall continuity was already investigated in 1910, with a study of the penetration of some salts into the root that provided evidence that several salts needed to pass through the endodermis symplast in order to reach the stele (de Rufz de Lavison, 1910). Later, many studies reported that the diffusion of fluorescent dyes or ions is blocked at the level of the endodermis and that this coincides with the presence of the CS (Clarkson and Sanderson, 1969;Robards and Robb, 1974;Singh and Jacobson, 1977;Peterson, 1987). Recently, studies in Arabidopsis employed propidium iodide (PI) as a tracer for the apoplastic route (Alassimone et al, 2010).…”
Section: Three Routes For Nutrients the Apoplastic Pathwaymentioning
confidence: 99%
“…Ions must first be absorbed into epidermal, cortical, and endodermal cells and then move through the symplast past the Casparian strip to enter the stele of roots with an intact and well developed endodermis (6,20,22,25). While much is known about the mechanism of ion transport into cells of the root cortex (7,10,11), the mechanism of ion transport from stelar parenchyma cells to xylem elements is poorly understood (1,12,13).…”
mentioning
confidence: 99%
“…It is a known that the endodermal Casparian strip blocks the free apoplastic passage of various ions, heavy metals and fluorescent dyes (Robards andRobb 1972, Nagahashi et al 1974). It is possible that the Casparian strip at exodermis may be functioning similarly, as a filter or barrier to apoplastic movement like the endodermis in juvenile roots (Peterson et al 1978(Peterson et al , 1982Peterson 1987, Lehmann et al 2000.…”
Section: Discussionmentioning
confidence: 99%